Perceived Clinical Competency, Confidence and Professionalism of Novice Nurses Participated in the New RN Residency Program - Kimberly H. Kim; Andrew Lee; Lynn Eudey (Issues and Development in Health Research Vol. 7, 2021)
The new RN residency program provides transitional experiences to integrate nursing knowledge, skills, and attitudes of newly graduated nurses before they assume the professional nurses’ roles. It also benefits students by improving clinical competence, confidence, and socialization skills. The study examined the levels of perceived clinical competency, confidence, and professional role development skills of 115 culturally diverse novice nurses enrolled in 12-15 weeks of a collaborative RN residency program at a state-funded California university during academic years 2009-2014. Descriptive pre-and post-program measures study assessed core competency and confidence of participants before and after the residency program using three instruments; a modified quality and safety education for nurses (QSEN) competency questionnaire, Preceptorship Experience Questionnaire, and Graduate Nurse Survey. Results show that, compared to the pre-program sum, participants report to perceive the significantly higher levels of the post-program sum of competency skills in applying QSEN concepts and nursing process cycles that include assessment, planning, implementation, and evaluation as well as professional role development. Interestingly, participants report feeling it is very important to develop a trusting relationship with their preceptor and a positive relationship with staff nurses. Participants also report perceiving a higher level of confidence in carrying out nursing care at the end of the program. Findings suggest that newly graduated nurses perceive the increased levels of clinical competency and confidence in their self-administered report after participating in the RN residency program.